2020
DOI: 10.3390/molecules26010013
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of µ-Opioid Receptor Agonists with Biased G Protein or β-Arrestin Signaling, and Computational Study of Conformational Changes during Receptor Activation

Abstract: In recent years, G protein vs. β-arrestin biased agonism at opioid receptors has been proposed as an opportunity to produce antinociception with reduced adverse effects. However, at present this approach is highly debated, a reason why more information about biased ligands is required. While the practical relevance of bias in the case of µ-opioid receptors (MOP) still needs to be validated, it remains important to understand the basis of this bias of MOP (and other GPCRs). Recently, we reported two cyclopeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Protein–ligand complexes from selected docked poses were minimized in explicit TIP3P water molecules and equilibrated by molecular dynamics. More details can be found in the literature [ 52 ] and in the experimental section. The overlay of KW-495 and KW-496 into KOP is illustrated in Figure S6 , and shows that the two peptide conjugates occupy the same cavity of the receptor, albeit with distinct orientations.…”
Section: Resultsmentioning
confidence: 99%
“…Protein–ligand complexes from selected docked poses were minimized in explicit TIP3P water molecules and equilibrated by molecular dynamics. More details can be found in the literature [ 52 ] and in the experimental section. The overlay of KW-495 and KW-496 into KOP is illustrated in Figure S6 , and shows that the two peptide conjugates occupy the same cavity of the receptor, albeit with distinct orientations.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, several studies supported that κ-OR plays an important role in cancer development by promoting or inhibiting tumor growth and metastasis and influencing patient prognosis. These observations demonstrated that κ-OR is upregulated in various types of solid tumors, such as liver, colon, non-small cell lung cancer, and other malignancies, and its expression is associated with cancer growth and a poor prognosis [24][25][26].…”
Section: Biological Effects 241 Effect Of the Amides On Cell Viabilitymentioning
confidence: 88%
“…Molecular dynamics simulations (MDS) reveal additional 7TMR conformations. Distinct intracellular pocket conformations have been observed in simulations of μOR complexes with a wide variety of ligands 21,[26][27][28][29] . We hypothesized that signaling efficacy is linearly proportional to the equilibrium population of these intracellular receptor conformations.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that signaling efficacy is linearly proportional to the equilibrium population of these intracellular receptor conformations. To test this hypothesis, we first performed simulations of μOR complexed with 11 ligands from a variety of chemical series, comprising the most comprehensive set of agonists in a single study to date (previous studies 21,[26][27][28][29] included up to 5 complexes). We tested this hypothesis by developing a machine learning model that categorizes configurations from MDS into conformations.…”
Section: Introductionmentioning
confidence: 99%